2011
DOI: 10.1371/journal.pone.0018508
|View full text |Cite
|
Sign up to set email alerts
|

Warming Can Boost Denitrification Disproportionately Due to Altered Oxygen Dynamics

Abstract: BackgroundGlobal warming and the alteration of the global nitrogen cycle are major anthropogenic threats to the environment. Denitrification, the biological conversion of nitrate to gaseous nitrogen, removes a substantial fraction of the nitrogen from aquatic ecosystems, and can therefore help to reduce eutrophication effects. However, potential responses of denitrification to warming are poorly understood. Although several studies have reported increased denitrification rates with rising temperature, the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 36 publications
9
103
0
9
Order By: Relevance
“…Climate will have a profound effect on the decline of soil available N and P [20]. Temperature may enhance the soil microbial process and soil biochemical processes, such as denitrification, which are positively related to temperature [21]. Tree species can have a strong influence on soil properties [22].…”
Section: Discussionmentioning
confidence: 99%
“…Climate will have a profound effect on the decline of soil available N and P [20]. Temperature may enhance the soil microbial process and soil biochemical processes, such as denitrification, which are positively related to temperature [21]. Tree species can have a strong influence on soil properties [22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the decreased dissolved oxygen in the sediments associated with higher temperatures would be beneficial to anaerobes, such as denitrifiers or anaerobic ammonia-oxidizing (anammox) bacteria. It has been observed that rates of denitrification and anammox in sediment vary with temperature changes (47,48). Since denitrification activity and anammox bacteria-related sequences have been detected in Lake Taihu sediment (49,50), it is likely that the interactions between N-cycling processes as well as the ammonium assimilation by heterotrophs (51) in sedi- ments result in the low concentrations of nitrate at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms responsible for higher P availability include higher mineralization rates and release from bottom sediments triggered by the higher temperatures. Concentrations of N, however, seem to decrease ( Figure 5C-E), which may partly be attributed to higher growth rates and thus greater nutrient uptake of phytoplankton, as well as increased bacterial denitrification rates [62]. Diatoms and cyanobacteria generally seem to benefit from higher water temperatures during summer, and diatoms from reduced nutrient conditions, while the effect on green algae is less pronounced (Figure 6D-F).…”
Section: Effects Of Increasing Temperatures and Reduced Nutrient Loadingmentioning
confidence: 98%